The International Society of Hypertension and World Hypertension League call on governments, nongovernmental organizations and the food industry to work to reduce dietary sodium - Campbell, Norman R. C. (2014)
The International Society of Hypertension and the World Hypertension League have developed a policy statement calling for reducing dietary salt. The policy supports the WHO and the United Nations recommendations, which are based on a comprehensive and up-to-date review of relevant research. The policy statement calls for broad societal action to reduce dietary salt, thus reducing blood pressure and preventing hypertension and its related burden of cardiovascular disease. The hypertension organizations and experts need to become more engaged in the efforts to prevent hypertension and to advocate strongly to have dietary salt reduction policies implemented. The statement is being circulated to national hypertension organizations and to international nongovernmental health organizations for consideration of endorsement. Member organizations of the International Society of Hypertension and the World Hypertension League are urged to support this effort.